EFEKTIVITAS PROGRAM CAR FREE DAY TERHADAP PENURUNAN KADAR NOx UDARA DI SURABAYA TAHUN 2017 - Rachmaniyah Rachmaniyah; Imam Thohari (Communication and Social Dinamics (CSD), 2017)
Motor vehicles contribute greatly to air pollution. The number of motor vehicles in Surabaya reached 1,827,806 units in 2010 while the increase of motor vehicles per year reached 30%. Surabaya City Government launched Car Free Day program with the aim to reduce and control exhaust emissions from motor vehicles. The purpose of this research is to find out the effectiveness of Car Free Day program to decrease NOx content in air. This research is descriptive with cross sectional approach. The data were collected by observation, field parameter measurement and NOx measurement at Car Free Day and Non Car Free Day (NCFD) at Kertajaya Street and Raya Darmo Street Surabaya. The data were then presented in the tabulation and were analyzed in descriptive form. The results of the average NOx concentration on Kertajaya Street at the time of CFD were 266.4 μg / Nm3 and at the time of NCFD was 409 μg / Nm3. Average NOx concentration on Raya Darmo Street at CFD was 298.4 μg / Nm3 and at the time of NCFD was 431,76 μg / Nm3. According to PP No.41 of 1999, it is stated that the rate of NOx in 1 hour measurement is 400 μg / Nm3. The decrease percentage of NOx concentration in Kertajaya Street was 34.86% and on Raya Darmo Street was 30,88%. Car Free Day program is not effective in lowering air NOx levels in Kertajaya Street and Raya Darmo Street Surabaya. It is recommended that the Surabaya City Government can add some point of the road as well as the addition of days for Car Free Day activities. Keywords: Efectiveness, Car free day, Pollutants NOx